2016
DOI: 10.2298/vsp150917111d
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries in hospitalized patients with schizophrenia

Abstract: Hospitalized patients with schizophrenia had twice as many caries and extracted teeth, and five time less filled teeth than healthy people. The patient’s age and taking antiparkinsonics were established as predictors of the increased DMF index in hospitalized patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(32 reference statements)
2
11
1
Order By: Relevance
“…913 Ninety percent of study participants presented with caries and the mean caries score (DMFT=5.2 [4.2]) for the entire study population was high, bringing our findings closer to studies conducted around the world. 14–17, 1922, 24, 25 The mean caries score was significantly higher among females psychiatric patients compared to males, which may be attributable to negligence of dental care in females compared to males. This is in line with the studies conducted previously that showed high prevalence of caries in females compared to males, 14, 24 though the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…913 Ninety percent of study participants presented with caries and the mean caries score (DMFT=5.2 [4.2]) for the entire study population was high, bringing our findings closer to studies conducted around the world. 14–17, 1922, 24, 25 The mean caries score was significantly higher among females psychiatric patients compared to males, which may be attributable to negligence of dental care in females compared to males. This is in line with the studies conducted previously that showed high prevalence of caries in females compared to males, 14, 24 though the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Dental caries is a major public health problem globally and it is the most widespread noncommunicable disease 6 . Previous studies have shown that people with several mental disorders have an increased prevalence of dental caries [7][8][9][10] . This can be explained by several reasons: mental disorders lead to lack of motivation, lack of oral hygiene, fear to visit a dentist, difficulty to access health services and adverse effects of antipsychotic medication, mainly xerostomia, could be also present 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Oral health is the part of general health that should not be separated from mental health. Several studies in the oral health of psychiatric patients in various countries denote that mental disorders and the use of such drug therapies as antipsychotic drugs can cause the improvement of prevalence and severity of oral diseases [3], [4].…”
Section: Introductionmentioning
confidence: 99%